SYSTEMS OF LINEAR EQUATIONS
AND INEQUALITIES
Week 04: Solving System of Linear Equations Algebraically
Prepared by: Jojo M...
A. Using the Substitution Method
Example 1

Solve the following system of equations:
x + 2y = 7

E. 1 y - 1

= 2x

E. 2

S...
B Using the Addition Method
Example 1
Solve by the addition method
3x + y = 10

E. 1

2x - y = 5

E. 2
C.Using Subtraction Method
D.Using Multiplication with the Addition Method

Solution :
Example 2
Solve:

2x + 3y = -1

E. 1

5x-2y = -12

E.2
Systems of linear equations weedk4 discussion
Systems of linear equations weedk4 discussion
Systems of linear equations weedk4 discussion
Upcoming SlideShare
Loading in …5
×

Systems of linear equations weedk4 discussion

263 views

Published on

read and study carefully....

Published in: Education, Technology, Business
  • Be the first to comment

  • Be the first to like this

Systems of linear equations weedk4 discussion

  1. 1. SYSTEMS OF LINEAR EQUATIONS AND INEQUALITIES Week 04: Solving System of Linear Equations Algebraically Prepared by: Jojo M. Lucion DISCUSSION To solve a system of linear equations algebraically, we must reduce the system to a single equation with only one variable. Do you still remember the properties of equality? Let us call the properties as the Golden Rule of Equations. Whatever you do unto one side of an equation, do the same thing unto the other side of the equation. Then the equation will remain true. In particular, you can: • • • • Add the same number to both sides - A.P.E. Subtract the same number from both sides - S. P. E. Multiply both sides by the same number - M.P.E. Divide both sides by the same number -D.P.E. Let us recall how to transform an equation with two variables to y = mx + b Transform each of the following equations to y = mx + b Now , are you ready to solve system of linear equations using the algebraic method?
  2. 2. A. Using the Substitution Method Example 1 Solve the following system of equations: x + 2y = 7 E. 1 y - 1 = 2x E. 2 Solution: • Solve E. 2 for y: y = 2x + 1 • Eliminate y in E.1 by substituting 2x + 1 for y: x = 7 + 2(2x + 1)= 7 x + 4x + 2 = 7 5x + 2 = 7 5x = 7-2 5x = 5 x equations: 2y x • + = 5 =1 5 Find the value of y when x = 1 by substituting 1 for x in either of the two original x + 2y = 7 1 + 2y = 7 2y = 7 - 1 2y = 6 y= 6 y= 3 2 Solution(1, 3)
  3. 3. B Using the Addition Method
  4. 4. Example 1 Solve by the addition method 3x + y = 10 E. 1 2x - y = 5 E. 2
  5. 5. C.Using Subtraction Method
  6. 6. D.Using Multiplication with the Addition Method Solution :
  7. 7. Example 2 Solve: 2x + 3y = -1 E. 1 5x-2y = -12 E.2

×